Feasibility of a high-PRotein Mediterranean-style diet and resistance Exercise in cardiac Rehabilitation patients with sarcopenic obesity (PRiMER): Study protocol for a randomised control trial. (October 2021) - McCullough, Deaglan; Kirwan, Richard; Butler, Tom; Perez de Heredia, Fatima; Thijssen, Dick; Lip, Gregory Y.H.; Mills, Joseph; Davies, Ian G.
Summary: Background: Cardiac rehabilitation (CR) is an essential component of long-term recovery following a cardiac event. Typical CR may not be optimal for patients presenting with sarcopenic obesity (SO) who present with reduced muscle mass and elevated adipose tissue, and may indicate greater cardiovascular disease (CVD) risk. Resistance exercise and high-protein diets are known to increase muscle mass, while Mediterranean-style diets have been shown to reduce CVD risk. A high-protein Mediterranean-style diet combined with resistance exercise intervention is yet to be trialled in cardiac rehabilitation populations. Objectives: Primary outcome: to determine the feasibility of such an intervention by investigating the perceptions, acceptance and adherence to a resistance exercise protocol and high-protein Mediterranean style diet in a UK cardiac rehabilitation population with SO. Secondary outcome: to trial this protocol ahead of a fully powered clinical study. Methods: Eligible cardiac rehabilitation patients will be randomised to one of the following: 1) a control group (standard CR), 2) high-protein Mediterranean-style diet, 3) resistance exercise group, or 4) both high-protein Mediterranean-style diet and resistance exercise group. The pilot study will last 12 weeks. Measures of body composition (dual energy x-ray absorptiometry) grip strength, CVD risk (e.g., fasting triglycerides, glucose, cholesterol) and dietary adherence will be assessed at baseline and after 12 weeks. To compare groups, a mixed model ANOVA (time x intervention) will be performed. Patient participant involvement throughout the development of this project will be used to determine the feasibility of a future, fully powered, randomised control trial. A feasibility questionnaire will help establish the proportion of eligible participants, their willingness to be randomised, response rates, and ethical considerations. Furthermore, focus groups, food tasting and telephone interviews will be conducted to assess the acceptability of recipes and exercise protocols provided. Discussion: This pilot trial will determine whether a fully powered, multi-centred randomised control trial in CR patients with SO can be implemented. The information received from patient involvement will be invaluable for identifying possible barriers to participation and tailoring interventions to participant needs, helping to increase the likelihood of long-term compliance to health-promoting lifestyle changes. Registration: This study is registered at clinicaltrials.gov (NCT04272073), registered on 17/02/2020, https://clinicaltrials.gov/ct2/show/NCT04272073 . Date and version: 28/12/20 version 3.0.